Crocus sativus dan Insomnia - Nur Sazaro Tudhur (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Crocus sativus L. from the Iridaceae family, commonly known as saffron, is a medicinal herb that is widely cultivated in Iran and other countries, such as India and China. The effect of saffron and its elements on anxiety and insomnia shows a promising result. The effect of saffron is similar to the activity of diazepam. Diazepam can be used as benzodiazepines, anxiolytics, analgesics, relaxants, and hypnotic agents. Saffron extracts and their constituents, safranal and crocin (crocin and crocetin hydrolysis products), are shown to affect various neuronal pathways that are relevant to sleep. Research shows that this effect affects the sleep rhythm and triggers for sleep